SISTEM PAKAR DETEKSI PENYAKIT DIABETES MELLITUS DENGAN MENGGUNAKAN PENDEKATAN NAÏVE BAYESIAN BERBASIS WEB (Studi Kasus: PUSKESMAS Kelurahan Grogol 3) - Riki Antoni (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Diabetes mellitus (DM) is a chronic disease that will last a lifetime and has a big impact on the quality of human life and requires quite large medical costs. Diabetes mellitus can trigger various dangerous disease complications and requires long-term treatment. Currently, there is no website that can replace the role of a doctor in diagnosing diabetes mellitus which can make it easier for the public to diagnose diabetes mellitus. To solve the problems above, it is necessary to build a web-based Expert System that can detect Diabetes Mellitus based on the symptoms that have been entered and provide recommendations in the form of information and solutions to the disease. One method that can be used to calculate probability is the Bayesian method. This method is an approach to uncertainty that is measured by probability, predicting future probabilities based on past experience. The system built uses the PHP programming language and MySQL database as storage media. Building an Expert System that is able to diagnose diabetes mellitus will really help patients in diagnosing diabetes mellitus earlier.